Management of Educational Facilities and Infrastructure in Improving The Quality of Learning at Widoro State Primary School - Hadi, Samsul; Afi Salsabila, Ananda; Mukti Rahayu, Esta Diana (Journal of Elementary School Education, 2024)
Management is an activity carried out together and through people and groups to achieve organizational goals. Improving the quality of education will be achieved if the teaching and learning process carried out in the classroom is truly effective and useful for achieving the expected knowledge, attitudes, and skills. Because basically, the teaching and learning process is the core of the overall educational process, among which the teacher is one of the important factors in determining the success of the teaching and learning process in the classroom. The function of managing facilities and infrastructure is very fundamental in improving the quality of learning, creating a socio-emotional climate, and managing group processes, so that the success of teachers in creating enabling conditions, and indicators of the teaching and learning process take place effectively. The study in this article provides an understanding to readers about the management of educational infrastructure, the educational infrastructure used by teachers in the learning process, and the management of the utilization of educational infrastructure in improving the quality of learning.